Tumor Size Is an Independent Prognostic Factor for Stage I Ovarian Clear Cell Carcinoma: A Large Retrospective Cohort Study of 1,000 Patients - Wu, Liangcai; Shi, Shuo; Sun, Hong; Zhang, Haiyan (Frontiers in Oncology, 2022)
Objective To investigate the prognostic value and stratification cutoff point for tumor size in stage I ovarian clear cell carcinoma (OCCC). Methods This was a retrospective cohort study using the Surveillance, Epidemiology, and End Results database (version: SEER 8.3.9). Patients diagnosed with stage I ovarian clear cell carcinoma from 1988 to 2018 were included for further analysis. X-Tile software was used to identify the potential cutoff point for tumor size. Stratification analysis, propensity score matching, and inverse probability weighting analysis were used to balance the potential confounding factors. Results A total of 1000 stage I OCCC patients were included. Using X-Tile, we identified 8 cm as the potential cutoff point for tumor size. After balancing the potential confounding factors, we found that tumor size was an independent prognostic factor for stage I OCCC. Patients with tumors smaller than 8 cm had a significantly better prognosis. Subgroup analysis showed that the micro-sized tumor group (max diameter ≤ 1 cm) had the best prognosis in stage I OCCC. Conclusions Tumor size is an independent prognostic factor for stage I OCCC, and 8 cm is a promising cutoff point for tumor size for risk stratification. Using tumor size in stratification management of stage I OCCC patients warrants further investigation.